Major heat shock gene of Drosophila and the Escherichia coli heat-inducible dnaK gene are homologous. - Bardwell, J C (1984)
The Escherichia coli dnaK gene is homologous to the major heat shock-induced gene in Drosophila (Hsp70). The primary DNA sequence of the entire protein-coding region of the dnaK gene was determined and compared with that of the Hsp70 gene of Drosophila. The two sequences are homologous; the dnaK gene could encode a 69,121-Da polypeptide, 48% identical to the hsp70 protein of Drosophila. The homology between the Hsp70 gene of Drosophila and the E. coli dnaK gene illustrates the remarkable conservation of the heat shock genes in evolution. In contrast to Drosophila and Saccharomyces cerevisiae, both of which contain multigene families related to the Hsp70 gene, hybridization analyses indicate that E. coli contains only a single Hsp70-related gene, dnaK. Hybridization between the DNA of an archaebacterium Methanosarcina barkeri and the Hsp70 genes of Drosophila, Saccharomyces, and E. coli has been detected, suggesting the existence of Hsp70-related genes in the three "primary kingdoms": eukaryotes, eubacteria, and archaebacteria.